Edukacyjny wymiar przestrzeni rekreacyjno-wypoczynkowych na przykładzie „placówek” Związku Pracy Obywatelskiej Kobiet - Piwowarczyk, Mirosław (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2021)
The Women Citizens’ Work Association was one of the most influential women’s organizations of the Sanation movement in the interwar Poland. It was active in the years 1928–1939. It had a clear ideological and political character that determined its goals and tasks. The most important among all the undertakings of the Union were: activation of women and their civic and state education, creating a “new type of Polish female citizen” – aware of her rights and civic obligations, interested in state affairs, independent, distinguished by a deep sense of responsibility for the state and participating in efforts to “raise ethical, cultural, economic and social level”. In practice, the most important educational task undertaken by the Union’s activists was the implementation of a new model of civic and state education of women.In this work, traditional and modern means, forms and methods of exerting educational influence were used. Effective forms of educational work included various types of summer facilities/camps: holiday, military-leisure, educational-recreational, wayfaring, organized in stationary establishments – shelters or boarding houses. It was assumed that the camps constitute a specific social and educational space, which has great educational qualities, effectively shaping the social, civic and state attitudes desired from the point of view of the Association’s goals. As part of the camp work, an effort was also made to deepen the cultural habits of the participants, shape their character, expand their knowledge of the state and society, and prepare them for their life in the community. It was also important to promote a healthy, hygienic lifestyle, allow all women to rest and regain health.78The camps were organized in a dozen or so attractive towns in Poland. There were dozens of different types of camp facilities, which were visited by several thousand women in total
Keywords: The Women Citizens’ Work Association; activation of women; civic education; leisure facilities; recreational facilities; holiday facilities; wayfaring camps